Molecular details of secretory phospholipase A(2) from flax (Linum usitatissimum L.) provide insight into its structure and function - Gupta, Payal (Sci Rep, 2017)
Secretory phospholipase A(2) (sPLA(2)) are low molecular weight proteins (12–18 kDa) involved in a suite of plant cellular processes imparting growth and development. With myriad roles in physiological and biochemical processes in plants, detailed analysis of sPLA(2) in flax/linseed is meagre. The present work, first in flax, embodies cloning, expression, purification and molecular characterisation of two distinct sPLA(2)s (I and II) from flax. PLA(2) activity of the cloned sPLA(2)s were biochemically assayed authenticating them as bona fide phospholipase A(2). Physiochemical properties of both the sPLA(2)s revealed they are thermostable proteins requiring di-valent cations for optimum activity.While, structural analysis of both the proteins revealed deviations in the amino acid sequence at C- & N-terminal regions; hydropathic study revealed LusPLA(2)I as a hydrophobic protein and LusPLA(2)II as a hydrophilic protein. Structural analysis of flax sPLA(2)s revealed that secondary structure of both the proteins are dominated by α-helix followed by random coils. Modular superimposition of LusPLA(2) isoforms with rice sPLA(2) confirmed monomeric structural preservation among plant phospholipase A(2) and provided insight into structure of folded flax sPLA(2)s.